2003
DOI: 10.1186/1477-7827-1-12
|View full text |Cite
|
Sign up to set email alerts
|

Effects of deletion of the prolactin receptor on ovarian gene expression

Abstract: Prolactin (PRL) exerts pleiotropic physiological effects in various cells and tissues, and is mainly considered as a regulator of reproduction and cell growth. Null mutation of the PRL receptor (R) gene leads to female sterility due to a complete failure of embryo implantation. Pre-implantatory egg development, implantation and decidualization in the mouse appear to be dependent on ovarian rather than uterine PRLR expression, since progesterone replacement permits the rescue of normal implantation and early pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(26 citation statements)
references
References 46 publications
(45 reference statements)
1
23
0
1
Order By: Relevance
“…SOCS proteins have been demonstrated to act as potent inhibitors of Prl signaling in different cellular systems in vitro (Helman et al, 1998;Pezet et al, 1999;Tomic et al, 1999;Lindeman et al, 2001) and we have established a physiological role for SOCS1 as a negative regulator of the prolactin pathway in the mammary gland (Lindeman et al, 2001). Targeted deletion of Prl and its receptor (PrlR) has revealed that these genes play an essential role in mammary and ovarian development and in the maintenance of pregnancy (Horseman et al, 1997;Ormandy et al, 1997;Grosdemouge et al, 2003). Other cytokines, including growth hormone and IL-6, which are also regulated by SOCS proteins, appear to exert key functions in these organs.…”
mentioning
confidence: 94%
“…SOCS proteins have been demonstrated to act as potent inhibitors of Prl signaling in different cellular systems in vitro (Helman et al, 1998;Pezet et al, 1999;Tomic et al, 1999;Lindeman et al, 2001) and we have established a physiological role for SOCS1 as a negative regulator of the prolactin pathway in the mammary gland (Lindeman et al, 2001). Targeted deletion of Prl and its receptor (PrlR) has revealed that these genes play an essential role in mammary and ovarian development and in the maintenance of pregnancy (Horseman et al, 1997;Ormandy et al, 1997;Grosdemouge et al, 2003). Other cytokines, including growth hormone and IL-6, which are also regulated by SOCS proteins, appear to exert key functions in these organs.…”
mentioning
confidence: 94%
“…All transfections were performed in triplicate and normalized with ␤-galactosidase activity (carried by pCMV-␤Gal, 0.1 g) for transfection efficiency. TRIzol reagent (GIBCO͞BRL) was used to extract total RNA from coculture cells; primers and RT-PCR conditions were as described (2,22,23).…”
mentioning
confidence: 99%
“…It is likely be involved in angiogenesis, e.g. of the ovary [15, 16] and testis [29]. Studies by other investigators [7, 8, 30] and our own group (unpubl.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of the two PRL-R forms varies in the CL depending on the oestrous cycle, on pregnancy and lactation [14]. CL-derived EC appear to be sensitive to PRL, because Gaytan et al [15] observed a higher proliferative activity of EC in the CL of pregnant rats than of cycling rats; even more supporting, Grosdemouge et al [16] reported on extensive inhibition of angiogenesis during CL development in mice with targeted disruption of the PRL-R gene. For these reasons, microvascular EC from the CL appear particularly promising for the study of PRL-R forms with angiogenic potentials, even more as endocrine gland-derived EC are found to be unique in their response to certain growth factors, e.g.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation